Relationtionship between neurological and psychological symptoms and occupational exposures - Seyedeh Negar Assadi (Gonabad University of Medical Sciences, 2018)
Environmental exposures of workplace may affect employees' health including the nervous and psychological systems. Aim of this study was to determine the effects of occupational factors on psychological and neurological systems in workplaces. This is historical cohort study on employees in low and high exposure groups. The study's tool was flexible interview, questionnaire and occupational factors measurement. Sick employees were followed until the end of treatment. Headache was higher in employees with high level of lighting. The relative risk was 1.45 (1.04-2.02). Dizziness was significantly more in the working hours in offices. The risk ratio for dizziness was 2.25 (1.80-2.33). Employees with high exposure to occupational factors were at higher risk for headache and dizziness. There is relationship between loss of concentration and age. The risk ratio was 1.63 (1.13-2.36). The results of this study indicated that people who exposed to occupational and environmental pollutants occupational might be a risk for some psychological and neurological symptoms such as headache and dizziness and impaired concentration would be increased by aging.